Exclusive public—an analysis of public participation in the site selection procedure for a repository for nuclear waste - Denk, Albert (Frontiers in Political Science, 2024)
The aim of this article is to highlight and conceptualize key aspects of social closures that impact the German nuclear waste management case. According to the German legislator, the public must be involved in the search for a final repository for high-level radioactive waste. De facto, however, almost the entire population of Germany is excluded. In this article, processes of social closure are identified which lead to this and more extensive problematic situations with regard to procedural gaps. The participatory claim of the procedure already contains indeterminacies, participation conditions and concrete exclusions that make broad participation impossible. Based on the analysis of social closures to the outside and to the inside, it is shown that this participation only includes extremely few, generally better-off citizens and does not meet the claim to represent the public. Above all, closure mechanisms have an external effect, due to the characteristics of a supposed separation between people and their natural environment, the nation-statehood, and a limitation to symptom control. Internal closures function due to ignorance of unequal social positions, nuclear-historical amnesia, and the decoupling of safety and justice. This article ends with the conceptual creation of an exclusive public, which describes a process of state instrumentalization of public participation.